THE EFFECTS OF PUMPKIN AND RED SWEET POTATO ON PHYSICO-CHEMICAL PROPERTIES AND SENSORY ACCEPTANCE OF THE FRESH PLANT-BASED ICE CREAM - Nguyet, Nguyen Thi Minh; Duong, Trinh Thi Thuy; Toa, Nguyen Kim; Tuong, Luu Cat (HUIT Journal of Science, 2024)
With the rise in healthy diets and growing concerns about the environment and health, plant-based ice cream has become attractive to those who want to avoid animal products, food synthetic preservatives and additives. Recently, carbohydrates have been used as stabilizers to create gel structures and retain large amounts of free water in the food system. This study aimed to investigate the impact of pumpkin (PP), red sweet potato (SP), and their mixture on the physicochemical properties and sensory acceptance of plant-based ice cream prepared with a base of liquid obtained during the cooking of Lima beans (called aquafaba) and coconut milk. The recipe for the fresh plant-based ice cream mixture (% wt. of aquafaba) was as follows: sugar 20%; citrus fiber 1%; coconut milk powder 12%; coconut oil 6%; vanilla 0.6%. Four different formulas, which included the addition of 35% of PP (PP35), 35% of SP (SP35) and 35% of a mixture (M35) of PP and SP in a 1:1 ratio (by wt.), and a control sample (CS) with no addition were examined for cream viscosity, overrun (OR), water holding capacity (WHC), texture properties, melting rate and sensory evaluation. The results showed that, due to the advantages of both PP and SP, the ice cream M35 had the lowest melting rate with the dripping loss significantly reduced by 43-45% (%wt.) compared to PP35 and SP35. Besides, the sensory evaluation score of M35 was the highest, so M35 was considered the optimal supplement formula. This study contributes to the use of natural emulsion stabilizers in plant-based ice cream.